IMPACT OF GCG AND FINANCIAL DISCLOSURE ON FIRM VALUE WITH ROA AS MODERATOR: A STUDY OF STATE-OWNED BANKS (2019-2023) - Hartika, Aprilia Yana; Bawono, Andy Dwi (International Journal of Cultural and Social Science, 2026)
This research examines the impact of Good Corporate Governance (GCG) and financial information disclosure on the company value of State-Owned Enterprises (BUMN) banks listed on the Indonesia Stock Exchange (IDX), with Return on Assets (ROA) as a moderating variable. Using a quantitative approach, the study applies multiple linear regression and moderation analysis on secondary data from annual reports and financial statements of 20 publicly listed state-owned banks from 2019–2023. Descriptive statistics, classical assumption tests, model accuracy tests, and hypothesis testing were employed. The results show that GCG positively and significantly influences company value, while financial information disclosure and ROA have no significant effect. Moreover, ROA does not moderate the relationship between GCG, financial disclosure, and company value. This suggests that for state-owned banks, corporate value is more influenced by governance quality and institutional trust than by short-term profitability or transparency levels. Strengthening GCG practices is vital for enhancing corporate value. Further research is recommended to explore additional variables.